Numerical simulation of subsynoptic-scale cyclogenesis around an idealized Antarctic continent - Carrasco Cerda, Jorge Fernando (My University, 2017)
A three-dimensional numerical model of 100 km horizontal resolution was used to simulate subsynoptic-scale cyclogenesis around an idealized Antarctic continent. The simulation resolved a series of subsynoptic-scale cyclones around the idealized continent. These cyclones form adjacent to the confluence zones of katabatic winds. Their movements indicate an eastward direction going away from their initial point of formation. Baroclinic instability appears as primary mechanism for the development of these cyclones.
Simulación numérica de ciclogénesis a escala subsinóptica alrededor de un continente antártico idealizado
Keywords: numerical model; katabatic winds; subsynoptic-scale; cyclones; instability